Quo Vadis, biotremology? - Hill, Peggy S. M.; Mazzoni, Valerio; Stritih-Peljhan, Nataša; Virant-Doberlet, Meta; Wessel, Andreas (Springer, 2022)
Since our first collaborative book in 2014, which also included the first suggestion for a name for our new scientific discipline of biotremology, our focus has shifted from studying vibrational communication in a few groups of arthropods, to studying vibrational behavior (so that cues could be included) and now to a focus on physiology, ecology, and evolution. During this time, our scope has dramatically increased, but so have the numbers of publications on biotremology, as have the numbers of biotremologists of all ages, representing all continents on the Earth except for Antarctica. Our range of taxa has also expanded to encompass nematodes to mammals and birds. In this first chapter, our international editorial team, which represents Italy, Slovenia, Germany, and the USA, has taken on the role of writers to introduce each of the other 22 chapters in a preview of what the reader will find within the book. We also have collaborated to address the question in our chapter’s title, “Quo vadis, biotremology?” Where are we going with this scientific discipline, and where would we aspire to go, if we had unlimited funding and unlimited years to our lives?